The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1055/s-0039-1677879
|View full text |Cite
|
Sign up to set email alerts
|

Free Tissue Transfer Penile Reconstruction

Abstract: Phalloplasty can be a challenging plastic surgery procedure associated with complications and unsatisfactory results. Phalloplasty has become an important procedure in the setting of trauma, partial or complete excision of the penis, and gender affirmation. Advances in microsurgery has expanded penile reconstruction through free tissue transfer techniques which include the radial forearm free flap, fibular osteocutaneous flap, anterolateral thigh flap, latissimus dorsi flap, scapular flap, and abdominal flaps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Muscular flaps used for neophallus creation can be obtained as a pedicled flap from anterolateral thigh (ALT) or as free flaps from the forearm (radial forearm free flap, RFFF) (Fig. 1a) [7,11]. Neourethra can be created using forearm skin flaps or vaginal or buccal mucosa in a "tube within a tube" fashion [12].…”
Section: Phalloplastymentioning
confidence: 99%
“…Muscular flaps used for neophallus creation can be obtained as a pedicled flap from anterolateral thigh (ALT) or as free flaps from the forearm (radial forearm free flap, RFFF) (Fig. 1a) [7,11]. Neourethra can be created using forearm skin flaps or vaginal or buccal mucosa in a "tube within a tube" fashion [12].…”
Section: Phalloplastymentioning
confidence: 99%
“…Phalloplasty techniques include the radial forearm free flap (RFFF), anterolateral thigh flap (ALT) (pedicled or free), and the musculocutaneous latissimus dorsi (MLD) (predominantly a non‐sensate flap). Additional, less common techniques include the fibular osteo‐cutaneous flap, superficial circumflex iliac artery perforator flaps (SCIP), and suprapubic phalloplasties [30]. Because of its reliable neurovascular anatomy and the ability to shape the tissue, the radial forearm flap remains the mainstay of phalloplasty procedures.…”
Section: Genital Reconstructive Surgeries/genital Gender‐affirming Su...mentioning
confidence: 99%
“…In addition to the scar left from graft harvesting, other complications include cellulitis, compartment syndrome, decreased strength, paresthesias, and neuromas. Overall outcome and patient satisfaction were generally favourable, with some studies showing up to 97% patient satisfaction and up to 60% reported being able to partake in penetrative intercourse following insertion of an IPP [ 39 ].…”
Section: Radial Forearm Free Flap Reconstructionmentioning
confidence: 99%